2017
DOI: 10.1038/ni.3688
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptional and epigenetic regulation of CD8+ T cell differentiation revealed by single-cell RNA sequencing

Abstract: SUMMARY During microbial infection, responding CD8+ T lymphocytes differentiate into heterogeneous subsets that together provide immediate and durable protection. To elucidate the dynamic transcriptional changes that underlie this process, we applied a single-cell RNA sequencing approach and analyzed individual CD8+ T lymphocytes sequentially throughout the course of a viral infection in vivo. Our analyses revealed a striking transcriptional divergence among cells that had undergone their first division and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
267
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 215 publications
(292 citation statements)
references
References 66 publications
(85 reference statements)
23
267
2
Order By: Relevance
“…This finding suggests that proteasome activity may be important in early CD8 + T cell fate specification, but may no longer play the same role in "fully differentiated" terminal effector or memory cells. In support of this possibility, we recently showed that early specification versus maintenance of CD8 + T cell fates may be regulated by distinct transcriptional programs (48). Using a single-cell RNAsequencing approach, we observed that 930 genes were differentially expressed between putative pre-memory and pre-effector cells at the first division, whereas 834 genes were differentially expressed between terminal effector and memory cells.…”
Section: Discussionmentioning
confidence: 81%
“…This finding suggests that proteasome activity may be important in early CD8 + T cell fate specification, but may no longer play the same role in "fully differentiated" terminal effector or memory cells. In support of this possibility, we recently showed that early specification versus maintenance of CD8 + T cell fates may be regulated by distinct transcriptional programs (48). Using a single-cell RNAsequencing approach, we observed that 930 genes were differentially expressed between putative pre-memory and pre-effector cells at the first division, whereas 834 genes were differentially expressed between terminal effector and memory cells.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, naive T cells showed co-deposition of H3K4me3 and H3K27me3 at promoter regions of genes important for cellular differentiation whereas genes associated with immune effector function lacked the permissive H3K4me3 modification, suggesting epigenetic mechanisms underlying CD8 + T cell differentiation and acquisition of effector function. Interestingly, a subset of effector-associated genes are rapidly, and in some cases, transiently induced after T cell activation (Best et al 2013; Kakaradov et al 2017), and may be marked by H3K4me2 modification in naive T cells (Russ et al 2014). Treatment of effector or memory T cells subsets with histone acetylase or deacetylase inhibitors modulates expression of effector-associated molecules (Araki, Wang, et al 2009) and affects memory function and potential (Northrop, Wells, and Shen 2008), further emphasizing a role for epigenetic changes in regulating gene expression at different stages of the T cell response (Figure 1A).…”
Section: Epigenetic Landscapes In T Cell Activationmentioning
confidence: 99%
“…This population expresses Cxcr5, Tcf7, Bcl6, has high proliferative capacity, and gives rise to effector cells in response to PD1 blockade [20, 35]. A recent study leveraged single-cell CD8 T cell transcriptomic data along a time course of acute viral infection (LCMV Armstrong) to discover two distinct transcriptional populations early in the time course [36]. Of the populations defined, one transcriptionally resembled terminal effectors and the other a memory-like state.…”
Section: Heterogeneity Of Cd8+ T Cell States Within Tumormentioning
confidence: 99%